Judicial Paradigm Clash: Comparative Analysis of the Application of the Anti-SLAPP Doctrine in the Protection of Environmental Activists - Valerie, Olivia (SIGn Jurnal Hukum, 2025)
The criminalization of environmental activists utilizing social media through Law Number 11 of 2008 has become a serious threat to public participation, demonstrably triggering inconsistencies in law enforcement. This research focuses on a critical analysis of the decisional disparity in the case of environmental activist Daniel Frits. Decision Number 14/Pid.Sus/2024/PN Jpa issued a criminal conviction, which was subsequently annulled entirely by Decision Number 374/Pid.Sus/2024/PT Smg, dismissing all charges against the defendant. Using a normative legal research method that integrates a statute approach and a case approach, this study performs an in-depth deconstruction and comparison of the legal reasoning (ratio decidendi) of both decisions. The results indicate that this decisional disparity stems from a fundamental clash between two conflicting judicial paradigms. The formalistic-positivistic paradigm adopted by the lower court was proven to have failed in applying the Anti-SLAPP doctrine. Conversely, the progressive-substantive paradigm embraced by the appellate court correctly affirmed the supremacy of activist immunity by applying Article 66 of Law Number 32 of 2009 as a justification defense, which nullified the criminal nature of the act. This finding indicates a fragility in the legal certainty for environmental activists, which is highly dependent on judges’ insight and courage. Therefore, it is necessary to formulate an ideal legal protection framework that does not merely rely on normative strength. This formulation also demands harmonization through the strengthening of institutional capacity and a cultural shift in law enforcement toward a greater orientation on substantive and ecological justice.